Utilization of Fermented Papaya and Apple Peels for Eco-Friendly Treatment of Waste Water - Sitti Nur Ilmiah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Unbalanced environmental conditions are a problem that must be overcome. The presence of pollutants is one of the conditions that cause the environment to be unbalanced so that it needs to be handled. Pollution of the aquatic environment needs attention because the impact given is quite troubling. An alternative that can be done in reducing pollutants in waters is to use liquid treatment from fermentation of organic waste. The content of fermented fruit peel waste is believed to reduce the content of water pollutants. The organic material fermentation method is used to remodel substrates from fruit and vegetable peels into certain products through chemical reactions that occur. The purpose of this study was to determine the pH, TSS, BOD, and COD values with and without papaya and apple peel fermentation liquid. The method developed in this research is descriptive quantitative. The results showed that the addition of papaya peel fermentation liquid to contaminated water resulted in pH, TSS, BOD, and COD parameter values of 2.56+0.18, 320.00+24.05 mg/L, 803.54+66.25 mg/L, and 2832.54+65.21 mg/L, respectively. The addition of apple peel fermentation liquid to contaminated water resulted in pH, TSS, BOD, and COD parameter values of 2.87+0.18, 770.00+38.20 mg/L, 1707.53+70.12 mg/L, and 11291.87+241.97 mg/L, respectively.